The development of Swiss sports clubs: Membership, volunteering, professionalization - Rahel Bürgi; Angela Gebert; Hanspeter Stamm; Markus Lamprecht (Bern Open Publishing, 2024)
Introduction The Swiss Sports Observatory has been conducting the national club survey since 1996. Every six years, the club managers of all sports clubs belonging to an association affiliated to Swiss Olympic are asked to complete a questionnaire. The survey is supported by Swiss Olympic, the Federal Office of Sport and other partners and provides information on the development of Swiss sports clubs, their structures and performance, as well as their strategies and prospects. The latest club survey was published at the end of 2023 (Bürgi et al., 2023). Methods The 2023 club survey is based on an online survey of 6,782 sports clubs. With a total of 18,229 sports clubs contacted, this results in a participation rate of 37.2%. The results were validated and their representativeness checked through various comparisons with other surveys (survey of the associations and the population surveys "Sport Schweiz 2020" and "Freiwilligen-Monitor"). Results The number of sports clubs - but not the number of active members - has fallen slightly in recent years. However, the large number of small clubs continues to characterize the Swiss club system. The high density of clubs ensures a wide range of activities, but also ties up a lot of resources and leads to increased fluctuation among members. The vast majority of active members as well as children and young people are active in medium-sized and large clubs. The number of active club members has remained stable for many years. There has been no decline in club memberships, but the clubs cannot profit from population growth and the sports boom. There are also significant changes in the club structure: clubs are growing among children but losing members among adults. This development has an impact on the recruitment of volunteers. Voluntary work therefore remains the foundation of club sport, but also the number one challenge. The problem cannot be solved with increased professionalization. Although there is more paid work in clubs today, the need for volunteers is still growing. Club budgets also place limits on professionalization. Staff cost is already the largest expense item today. The financial situation of Swiss sports clubs has not generally deteriorated in recent years. However, it has not been possible to tap into new sources of income either and membership fees cannot be increased at will. Discussion/Conclusion Overall, Swiss sports clubs have coped well with the various challenges of recent years. At the same time, the proportion of clubs facing problems that threaten their existence is increasing. Only with the active further development of club work and differentiated approaches to solutions, which help to meet the growing demands placed on clubs and the associated increased need for volunteers and paid staff, will clubs remain a central pillar of Swiss sport in the future (Lamprecht & Nagel, 2022). References Bürgi, R., Lamprecht, M., Gebert, A. & Stamm, H. P. (2023). Sportvereine in der Schweiz 2022. Entwicklungen, Herausforderungen und Perspektiven [Sports clubs in Switzerland in 2022: Developments, challenges and prospects]. Swiss Olympic. Lamprecht, M. & Nagel, S. (2022). Sportsoziologie: Einführung [Sociology of sport: Introduction]. Nomos.